1997
DOI: 10.1089/hum.1997.8.12-1491
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Retrovirus-Mediated Gene Transfer into Rat HepatocytesIn Vivo

Abstract: We have used high-titer (10(8) ffu/ml) recombinant retroviral vectors to transfer the beta-galactosidase (beta-Gal) gene to rat hepatocytes in vivo. In animals injected twice in the portal blood stream the next day after partial hepatectomy, half of the hepatocytes (46 +/- 17%) expressed the marker at the end of liver regeneration. The number of positive cells closely correlated with the viral titer as well as with beta-Gal enzymatic activity present in the whole liver. Because genes transferred via retroviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 19 publications
6
43
1
1
Order By: Relevance
“…Many different gene delivery methods are available including cationic lipid-based DNA transfection [44][45][46][47][48][49] and retroviral and adenoviral gene transfer vectors; [50][51][52][53][54][55] however, the use of these methods for hepatocytes has not been effective because hepatocytes do not divide, are highly susceptible to toxicity, and transfection efficiencies in hepatocytes are extremely low (HC Isom, unpublished data). 11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Many different gene delivery methods are available including cationic lipid-based DNA transfection [44][45][46][47][48][49] and retroviral and adenoviral gene transfer vectors; [50][51][52][53][54][55] however, the use of these methods for hepatocytes has not been effective because hepatocytes do not divide, are highly susceptible to toxicity, and transfection efficiencies in hepatocytes are extremely low (HC Isom, unpublished data). 11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Asialofetuin (AF), a glycoprotein having triantennary galactose terminal sugar chains, is known as an excellent ligand molecule selectively recognized by ASGPr. 2 For liver gene delivery, both virus-mediated [3][4][5] and non-viral systems have been considered. Although some of the virus-mediated gene transfer systems have been found to be quite effective, their usefulness is limited, given that they induce an immune response, leading to the rapid rejection of transduced cells.…”
Section: Introductionmentioning
confidence: 99%
“…Liver is an important target organ for gene delivery due to its function in synthesizing many serum proteins and its involvement in numerous genetic and acquired diseases. A variety of vectors have been used for introducing genes into the liver, including recombinant retrovirus, [1][2][3][4][5] adenovirus, 6-10 adeno-associated virus, [11][12][13] and nonviral vectors such as cationic polymers, [14][15][16] liposomes, 17,18 and reconstituted chylomicron remnants. 19 Although significant progress has been made in demonstrating successful gene delivery to the liver, a number of remaining difficulties and technical problems are associated with each of these methods.…”
Section: Introductionmentioning
confidence: 99%